Proving Innocence: The Petitions of Scholars for Reinstating Molla Mehmed Masûm, The Qadi of Trikala - Hüseyin Örs; Uğur Öztürk (İslam Tetkikleri Dergisi)
In this article, we examin the petitions written by forty-one high-ranking scholar-bureaucrats and sheiks in 1007/1598 for the reinstatement of Molla Mehmed Masûm Efendi who was deposed before completing his term while he was the qadi of Trikala in 1006/1598. These petitions, which were written under the leadership of Hoca Sadeddin Efendi and had almost the same content, were given by Mehmed Dâğî, the sheikh of Murad III, toValide Sultan Safiye Sultan, and probably she was asked to convey them to Mehmed III. Having been written in a period when the influence of the eunuchs and valide sultans increased in bureaucratic appointments which started with the appointment of Hoca Sadeddin Efendi as the head of the ulemâ by Murad III, these petitions are the interesting examples showing the bureaucratic and political change in the Ottoman Empire in the last quarter of the 16th century. In the article, the relations of Mehmed Dâğî, Safiye Sultan and Hoca Sadeddin, who led to write the petitions and to deliver them, are briefly discussed within the framework of the eunuchs and pashas of the period. Afterwards, the life of Molla Mehmed Masûm Efendi, about whom the petitions were written, is presented in general, in the light of the information from Hadāiq, the ruznamçes and the petitions. The last part of the article consists of a general evaluation of the petitions and the biographies of the people who wrote the petitions and the texts of the petitions.